Disegno dell'architettura Appunti per la didattica - Puma, Paola (Strumenti per la didattica e la ricerca, 2003)
The book was conceived as a collection of lectures given to students of Architectural Drawing courses and is intended as an orientation tool among the different fields of the discipline: from the preparatory phase of training to graphics, to the application of the principles of geometric representation, to conventional technical representation of architecture. In addition to the invention drawing, ample space is dedicated to survey drawing, applied first to the depicted architecture and then to the real city. Due to the character of the volume, intended as a learning tool, the texts are presented in the form of working notes with the main purpose of illustrating the pictures.